DFT Studies on the Effects of Functionalization on the Electronic and Optical Properties of 2,7-di-(N,N-diphenylamino)-9,9-dimethyl-9H-fluorene (ChemRxiv, 2024)
Density functional theory (DFT) calculations using B3LYP and 6-311+ G(d,p) basis set were performed to investigate the effect of functionalization on the electronic and optical properties of 2,7-di-(N,N-diphenylamino)-9,9-dimethyl-9H-fluorene (DDF). Four derivatives with various combinations of nitro and methoxy functional groups denoted as DDF2o, DDF2n, DDF4o, and DDF4n, were used in the investigation. Conformational studies of the DDF2n molecule revealed only minute energy differences among conformers in the total energy, HOMO, and LUMO energy, however, the different orientation and dipole moments may affect the device performance. Furthermore, the nitro-modified DDF derivatives have absorption spectra in a region of greater solar photon abundance. As the LUMO is located to the nitro moieties, often as strong anchoring groups, the nitro-modified DDF molecules could be excellent dye candidates for dye sensitized solar cells and for organic solar cells.